2001
DOI: 10.1139/cjz-79-2-303
|View full text |Cite
|
Sign up to set email alerts
|

Blood metabolites as indicators of nutrient utilization in fasting, lactating phocid seals: does depletion of nutrient reserves terminate lactation?

Abstract: Metabolites of lipid (free fatty acids (FFA) and β-hydroxybutyrate (βHBA)) and protein (blood urea nitrogen (BUN)) oxidation were measured during lactation in 18 female grey seals (Halichoerus grypus) and 6 female hooded seals (Cystophora cristata) as indicators of nutrient depletion and possible cues for pup weaning. FFA levels were high during lactation in both grey seals (51.2 ± 2.3 mg·dL -1 ) and hooded seals (67.0 ± 8.1 mg·dL -1 ), and levels were primarily related to the rapid lipid mobilization required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…by investigating metabolite trends leading up to weaning; Mellish & Iverson, 2001;Watson, Pomeroy, Al-Tannak, & Kennedy, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…by investigating metabolite trends leading up to weaning; Mellish & Iverson, 2001;Watson, Pomeroy, Al-Tannak, & Kennedy, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has demonstrated that female seals may adjust their reproductive output between years, when faced with changing environmental conditions prior to the lactation period, in order to maximize lifetime reproductive output (Bowen et al, 2015; Desprez et al., 2018; Kalberer, Meise, Trillmich, & Krüger, 2018; McMahon et al., 2016; Pomeroy et al., 1999; Smout et al., 2020), but research has yet to reveal the mechanism for terminating lactation in grey seals (e.g. by investigating metabolite trends leading up to weaning; Mellish & Iverson, 2001; Watson, Pomeroy, Al‐Tannak, & Kennedy, 2020). Extended time spent applying a non‐compensatory energy strategy may result in a heightened energy debt, forcing those individuals to terminate their breeding attempt and possibly also skip the following breeding season to extend their recovery time (Pomeroy et al., 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of blood metabolites and metabolic hormones in pinnipeds have focused on the physiology of fasting adaptation and determination of nutritional status in wild populations for health assessment (Costa and Ortiz 1982;Castellini and Rea 1992;Roletto 1993;Hall 1998;Mellish and Iverson 2001;Trumble et al 2006;Crocker et al 2012). However, limited research has investigated the response to realimentation in these fasting adapted species (Richmond et al 2010;Dailey et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Serum metabolites are often used to indicate the overall condition and health status of animals in clinical settings such as rehabilitation. Blood metabolites such as blood urea nitrogen (BUN), total protein, triglycerides, and glucose provide valuable information about the nutritional status of an animal based upon the types of energy sources (protein, lipid, carbohydrate) being utilized (Bossart et al 2001;Mellish and Iverson 2001;McCue 2010).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Typically, elevated EGP is required in other mammals to support milk production ( Mohammad et al ., 2009 ). Glucose may thus be higher in grey seals earlier in lactation to support high milk output ( Mellish et al ., 1999 ; Mellish and Iverson, 2000 ). The reduction in circulating glucose later in lactation may reflect decreased EGP to protect protein reserves.…”
Section: Discussionmentioning
confidence: 99%